Anemia among pregnant women attending antenatal clinic at a secondary health care facility in district Faridabad, Haryana - Shashi Kant; Sumit Malhotra; Partha Haldar; Ravneet Kaur; Rakesh Kumar (Wolters Kluwer Medknow Publications, 2019)
Background: India confronts a high burden of anemia among pregnant women, that contributes to significant morbidity and mortality for mother and child. Anemia Mukt Bharat strategy launched by Government of India envisages provision of variety of facility-based interventions for management of anemia in pregnancy. Secondary care hospitals prescribe injectable iron treatment for moderate anemia and blood transfusion services for severe anemia. Objective: To estimate the magnitude and severity of anemia among pregnant women when they presented themselves for the first time at the antenatal care clinic of a secondary care hospital so as to forecast adequate supplies of medicines for managing anemia. Materials and Methods: This was a descriptive study using routinely maintained hospital clinical records during the years 2013-2015. It was conducted in a subdistrict hospital, Ballabhgarh in Faridabad district of Haryana state. Hemoglobin (Hb) level was routinely measured at first visit for all pregnant women using BC-3000 plus autohematology analyzer. Anemia in pregnancy was considered when Hb concentration was <11.0 g/dL. Results: The Hb level at first visit was available for 13,467 women during the study period. The mean Hb level (standard deviation) was 9.3 g/dL (1.3). The proportion of anemic pregnant women was 91.3% (95% confidence interval [CI]: 90.8, 91.7). The most common category of anemia was moderate anemia 62.5% (95% CI: 61.6, 63.2). Conclusion: We found a very high prevalence of anemia in pregnant women presenting to a secondary care setting of a North Indian hospital during their first visit to the facility during the antenatal period.